Traffic management with elephant flow detection in software defined networks (SDN) - Hnin Thiri Zaw; AungHtein Maw (Institute of Advanced Engineering and Science, 2019)
Multipath routing is to distribute the incoming traffic load among available paths between source and destination hosts. Instead of using the single best path, multipath scheme can avoid the congested path. Equal Cost Multi-Path (ECMP) performs the static traffic splitting based on some tuples of the packet headers. The limitation of ECMP does not consider the network parameters such as bandwidth and delay. Unlike the traditional networks, Software-Defined Network (SDN) has many advantages to support dynamic multipath forwarding due to its special characteristics, such as separation of control and data planes, global centralized control, and programmability of network behavior. In this paper, we propose a new architecture design for dynamic multipath-based traffic management approach in the SDN, which comprises of five components: detecting long (elephant) flow, computing shortest paths, estimating end-to-end delay and bandwidth utilization, calculating least cost path and rerouting traffic flow from the ongoing path to the best path. The simulation environment is created through the usage of Mininet emulator and ONOS controller. The evaluation outcomes show that the proposed traffic management method outperforms the ECMP and reactive forwarding method for both TCP and UDP traffic.